1993
DOI: 10.1063/1.355297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of strain energy on the preferred orientation of TiN thin films

Abstract: The effects of strain energy on the preferred orientation of TiN thin films were investigated. In the TiN film deposited by plasma-enhanced chemical-vapor deposition with a power of 50 W, the overall energy of the film mainly depended on the surface energy because its strain energy was relatively small. The preferred orientation of the film corresponded to the plane with the lowest surface energy, i.e., (200). However, in the TiN film deposited by rf sputtering with a power of 200 W, the overall energy of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
149
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(159 citation statements)
references
References 18 publications
5
149
1
Order By: Relevance
“…According to the above equation, the particle size must be the largest in the case of the argon-nitrogen gas mixture as the atomic diameter of argon is the largest among those of the two gaseous environments [42,43]. In this research, the particle size calculated by XRD and AFM conforms to the expectations from the above equation.…”
Section: Effect Of Different Sputtering Gasessupporting
confidence: 50%
“…According to the above equation, the particle size must be the largest in the case of the argon-nitrogen gas mixture as the atomic diameter of argon is the largest among those of the two gaseous environments [42,43]. In this research, the particle size calculated by XRD and AFM conforms to the expectations from the above equation.…”
Section: Effect Of Different Sputtering Gasessupporting
confidence: 50%
“…14,15,27) In other words, when the coating is thin, the strain energy of the coating structure is very low and negligible. Conversely, the surface energy is high and important because surface energy does not vary with the coating thickness 14,15) ; therefore, the texture of the coating consists of planes which have the lowest surface energy and highest strain energy to compensate the shortage of strain energy and make a balance between surface and strain energies. 14,15,27) h layer has about 98 wt% of zinc and in hcp structure of this element, (00.2) planes have the lowest surface energy and the highest strain energy.…”
Section: Crystallographic Texture Of the Sheetsmentioning
confidence: 99%
“…10) It has been reported that coating thickness may influence on the texture of the coatings, 14,15) formability and mechanical properties, 1) coefficient of friction 1,2) and corrosion resistance 16) of coated sheets. But, these effects have not been adequately clarified and there is not sufficient literature on this subject, particularly quantitative data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the texture of cubic titanium nitride is a decisive factor for the technical quality of the coatings, as the u Fax: +49-551-39-4493, E-mail: pschaaf@uni-goettingen.de texture influences strain development and finally crack formation and propagation. Some investigations on texture and strain development in relation to the process parameters have been reported in the literature [12][13][14].…”
Section: Introductionmentioning
confidence: 99%